KARAKTERISTIK PERILAKU HYGIENE PENJAMAH MAKANAN DI INSTALASI GIZI RSU GMIM PANCARAN KASIH MANADO - Grace K. L. Langi; Daniel Robert; Henry S. Imbar (POLTEKKES KEMENKES MANADO, 2017)
Processed food at the Hospital is expected to help the healing process of patients. However, foods that should help heal can bring disease if the cultivating environment is not hygiene. The purpose of this research is to know the behavioral characteristic of hygiene of food handler in nutrition installation of RSU Gmim Pancaran Kasih Manado. Descriptive crossectional study with expert subject, ie food handler Determination of the number of samples that is the population of 11 people. Data collection techniques were conducted with questionnaires. Data were analyzed descriptively quantitative. The results showed that, food processor in Nutrition Installation General Hospital GMIM Pancaran Kasih Manado with the most age categories 40 to 49 years of 6 people, 5 elementary school education, and the majority pengolah gender of women. The conclusion of this study is that the hygiene behavior of food handlers or food processor categories is sufficient, with characteristics of age, and level of education.